Waste management problems that occur in Nagori Parik Sabungan with the LISA method (See Pick Take) - Meutia, Amalia; Siregar, Suri Mutia; Sinulingga, Samerdanta; Marlina, Lisa (Talenta Publisher, 2019)
This service aims to shape the behavior of LISA (See Garbage Take) in the community in Alam Nagori Parik Sabungan, so that it can help improve environmental hygiene in the village area and instill clean habits in children. Formation of LISA behavior is done by modifying economic token type behavior. An economic token is a method in which a person or group of people can get a token every time he displays the desired behavior. The series of service activities was held for approximately 29 days. As a result, 50% of child participants have understood the adverse effects of improper waste handling, and 100% of child participants have been able to display LISA behavior during activities